PathScore: a web tool for identifying altered pathways in cancer data. (8th August 2016) - Gaffney, Stephen G.; Townsend, Jeffrey P.
Abstract : Summary: PathScore quantifies the level of enrichment of somatic mutations within curated pathways, applying a novel approach that identifies pathways enriched across patients. The application provides several user-friendly, interactive graphic interfaces for data exploration, including tools for comparing pathway effect sizes, significance, gene-set overlap and enrichment differences between projects. Availability and Implementation: Web application available at pathscore.publichealth.yale.edu. Site implemented in Python and MySQL, with all major browsers supported. Source code available at: github.com/sggaffney/pathscore with a GPLv3 license. Contact: stephen.gaffney@yale.edu